Insecticidal Activity and Phytochemical Profiles of Avicennia marina and Excoecaria agallocha Leaves Extracts - Rozirwan Rozirwan; Muhtadi Muhtadi; Tengku Zia Ulqodry; Redho Yoga Nugroho; Nadila Nur Khotimah; Fauziyah Fauziyah; Wike Ayu Eka Putri; Riris Aryawati; Che Abd Rahim Mohamed (Marine Science Department Diponegoro University, 2023)
Toxic bioactive compounds can be obtained from various mangrove plants that have the potential to be developed in agriculture as bioinsecticides. The coast of South Sumatra has relatively abundant Avicennia marina and Excoecaria agallocha vegetation. This study was conducted to analyze the bioactivity of insecticides and the phytochemical profiles of mangrove leaves A. marina and E. agallocha was extracted with methanol, ethyl acetate, and n-hexane from the most toxic extract fraction. Samples were obtained from the Barong River in Sembilang National Park, Banyuasin Regency. The insecticidal activity of the samples was carried out on Gryllus bimaculatus and Tenebrio molitor. Furthermore, the phytochemical profile was analyzed using GC-MS. Based on the results of insecticidal activity on G. bimaculatus, the respective LC50 values of A. marina and E. agallocha extracts for the hexane fraction were 12,562 mg.L-1 and 15,464 mg.L-1, ethyl acetate 9,986 mg.L-1 and 10,292 mg.L-1, methanol 6,454 mg.L-1 and 6,969 mg.L-1. Whereas in T. molitor, the LC50 values for the hexane fraction were 10,682 mg.L-1 and 11,070 mg.L-1, ethyl acetate 9,065 mg.L-1 and 9,269 mg.L-1, methanol 4,799 mg.L-1, and 5,408 mg.L-1. The results of GC-MS analysis on the methanol extract of A. marina leaves which contained phytochemical compounds such as alcohol, lauric acid, myristic, linoleic, elaidate, stearate, endogenous, olead, phthalic ester, and siloxane. Based on the insecticide toxicity category, the insecticidal activity of both A. marina and E. agallocha leaves extracts were low and non-toxic. Further research is needed regarding variations in anti-insecticide of mangrove extract measurements in the future studies.